Clinical-epidemiological characteristics and temporal trend of new cases of grade 2 disability leprosy in the state of Maranhão, Brazil, 2011- 2020 - Rodolfo José de Oliveira Moreira; Janaína Miranda Bezerra; Floriacy Stabnow Santos; Lívia Maia Pascoal; Leonardo Hunaldo dos Santos; Marcelino Santos Neto (Ministério da Saúde do Brasil, 2023)
Abstract Objective: to describe the clinical and epidemiological characteristics of new cases of grade 2 disability leprosy and to analyze its trend in the state of Maranhão, from 2011 to 2020. Methods: this was a descriptive cross-sectional and ecological time-series study, using data from the Notifiable Health Conditions Information System. A descriptive analysis of the event was carried out according to the sociodemographic and clinical-laboratory characteristics of the cases. The temporal trend of event incidence was analyzed using Prais-Winsten regression. Results: of the 2,147 cases, 71.5% were male, 48.9% had up to 8 years of schooling, 66.5% were of mixed race/color, 95.5% had the multibacillary form, 58.8% were borderline, 32.3% had negative bacilloscopy at diagnosis. There was a stationary trend in the state and a falling trend in the São Luís Health Region (annual percentage change = -64.4%; 95% confidence interval: -73.7;-51.9). Conclusion: incidence trend was stable in the state of Maranhão and falling in São Luís.